Ablasi Frekuensi-Radio pada Takikardia Atrium Fokal di Sinus Koronarius - Muhammad Reza; Dicky A A Hanafy; Yanuar B. Hartanto; Sunu B Raharjo; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2016)
Focal atrial tachycardia (AT) is defined as atrial activation originating from a discrete focus with centrifugal spread. Available information suggests that focal activity can be caused by automaticity, triggered activity, or microreentry. Generally, AT response poorly to medication but can be treated by radiofrequency ablation with high long-term success. Focal AT represents approximately 3% to 17% of the patients referred for supraventricular tachycardia (SVT) radiofrequency ablation (RFA). Electrophysiology study is important to correctly diagnose the mechanism of the SVT before RFA is performed. Observation and several pacing maneuver could be done to identify the mechanism of SVT.A 54 year old female came with chief complaint of palpitation. During palpitation her ECG showed narrow complex regular tachycardia with the P-wave that was difficult to ascertain clearly. Electrophysiology study showed VA interval 130 ms, differences between VA interval during tachycardia and VA interval during RV pacing was 55 ms, no advanced in atrial activation, difference between ventricular post pacing interval (PPI) and tachycardia cycle length (TCL) was 130 ms, ventricular pacing during tachycardia results in V-A-A-V response before tachycardia resumes, and showed concentric atrial activation with earliest point at CS 9-10, indicating an AT from coronary sinus origin. AT was terminated during the RFA.Electrophysiology study is important to correctly diagnose AT, especially when P-wave during tachycardia in the surface ECG is uncertain. Several pacing maneuver during electrophysiology study can be very helpful to verify the diagnosis of AT.